Answer:
the length of the unknown leg is 10 cm
Explanation:
Use the Pythagorean theorem to solve the problem. The theorem states that the square of the hypotenuse equals the addition of the squares of the two legs:
![hyp^2=leg_1^2+leg_2^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/3e7lymkipm93gomf96e3zrhbft4jb3a2kw.png)
since we know the length one of the legs (24 cm) and also of the hypotenuse (26 cm), we can solve for the unknown leg in the equation above:
![hyp^2=leg_1^2+leg_2^2\\(26\,cm)^2=(24\,cm)^2 +leg_2^2\\leg_2^2 = (26\,cm)^2-(24\,cm)^2 \\leg_2^2=100\,cm^2\\leg_2=√(100\,cm^2) \\leg_2=10\,cm](https://img.qammunity.org/2021/formulas/mathematics/high-school/i2uu95clpexym3euk6sp8n24g0mlsg67rr.png)
Therefore, the length of the unknown leg is 10 cm.